Attack the enemy silently in its own den: SIGS - Spray-induced gene silencing, a novel approach to contain pathogens: SPRAY-INDUCED GENE SILENCING - A NOVEL APPROACH TO CONTAIN PATHOGENS - PAYAL PATWARI; V DINESH KUMAR (Journal of Oilseeds Research, 2021)
RNAinterference (RNAi) technology is considered an alternative tool to develop more environmentally friendly broad-spectrumpesticides in agriculture. In this approach, sequence-specific knockdown of gene targets in pests and pathogensusing double-strandedRNA(dsRNA) is utilized. Two different dsRNAapplicationmethods, host induced gene silencing (HIGS) and spray induced gene silencing (SIGS) are being followed. HIGS involves developing transgenic plants that produce the intended dsRNA which will be delivered into the pests when they feed or grow on the transgenic plants, while in SIGS the dsRNAs applied topically on the plants will be taken up by the target organisms. Once the dsRNA is in the target organism, the host RNAi cellular machinery will be used to silence the target genes. SIGS has been applied now against many pests and diseases in different crops and has given promising results. With the development of tools that facilitate economic production of large scale dsRNA and improve the stability and longevity of the sprayed dsRNAs on the plant surface, SIGS is a promising technology that could be adopted across crops and against different pests and pathogens. In this research update, we provide a summary of the recent developments in the area of SIGS with an emphasis on the examples of fungal pathogen control.